Coping strategies for bullying: a phenomenology of student perceptions - Nurhayati, Riana (Universitas Negeri Yogyakarta, 2024)
Efforts to reduce bullying in schools can be made by making strategies. However, so far, the strategies to overcome bullying are still seen from the teacher's point of view, and we need to see strategies to overcome bullying from students' perceptions. This study aims to find students' strategies for overcoming bullying. This research uses a qualitative approach with the type of phenomenology. The informants were high school and vocational high school students in Java. Data were collected through interviews, forum group discussions, and open-ended questionnaires. Data analysis used interactive analysis techniques. Data validity used triangulation of sources and techniques. The results showed that students' strategies to overcome bullying were carried out through social environment, internal factors, and external factors. The most effective strategies to overcome bullying are reporting to parents, teachers, or other students, being indifferent, establishing positive friendships, and focusing on the goals to be achieved. Supporting factors for the success of this strategy are the support system, guidance and counseling, and school socialization regarding anti-bullying. The inhibiting factors are school rules that still need to be firm, school culture that has not changed, and there is still an assumption that bullying is regular.Keywords: strategies bullying, phenomenology, student perceptions